Implementasi Manajemen Strategik Berbasis POAC dalam Meningkatkan Mutu Peserta Didik: Studi Kasus pada Dua PKBM di Kota Bekasi - Nitro, Nitro; Abdurrahman, Nana Herdiana (Cetta: Jurnal Ilmu Pendidikan, 2025)
Community Learning Centres (PKBM) are non-formal educational institutions that expand access to education for marginalised communities. This study applied a qualitative case study approach at PKBM Cikal Bangsa and PKBM A. Ridha in Bekasi City, conducted over a three-month period. Data were collected through in-depth interviews with ten informants, participatory observations, and analysis of institutional documents. The study employed the POAC (Planning, Organising, Actuating, Controlling) framework as an analytical tool to examine institutional management practices. Findings show that both PKBMs implemented participatory planning, adaptive staff organisation, flexible programme delivery, and structured monitoring and evaluation. These practices enhanced student engagement, learning discipline, and academic progress. Institutional success was supported by collaborative leadership, active community participation, and management strategies tailored to students' socio-economic conditions. Variations in management practices between the two centres reflected differing levels of implementation effectiveness. The study contributes to the theoretical understanding of strategic management in non-formal education and offers practical guidance for PKBM managers and policymakers in developing context-sensitive, sustainable management models.